Personalized Learning Environment (PLE) Experience In The 21st Century: Review Of Literature - Che Ku Mohd, Che Ku Nuraini; Shahbodin, Faaizah; Che Pee @ Che Hanapi, Ahmad Naim (2014)
The needs and responsibilities of the student‟s role in the 21st century have changed dramatically in the era of technology and globalization. The education should welcome the new trends which would be the parts and parcels of it. For achieving the aims and objectives of education, the teachers and the students may work in collaboration. This paper aim to review out about Personalized Learning Environment (PLE), how to build a PLE, PLE framework, issues and challenges in PLE, roles of student in PLE, the implications of PLE and also the future of PLE. PLE enables learners to organize their learning, provides the freedom to choose content, and allows communication and collaboration with others easily. In addition, PLEs enable learners to continue learning after formal courses have ended, and make lifelong learning possible. Keywords-Personalized Learning, 21st century, Technology, Education, ICT